Способ удаления облученного материала с плиты ядерного реактора - Гаврилов П. М. Петр Михайлович; Галузо Л. Б.; Изместьев А. М.; Мещеряков В. Н.; Романов О. Н.; Шидловский В. В. Владимир Владиславович; Цыганов А. А.; Чуканов В. Б.
опубл. 20.08.05